Development of PISA-like Math Tasks in the Context of Musi Rawas District through Lesson Study System - Anna Fauziah; Viktor Pandra (Universitas Sriwijaya, 2023)
This study aims to produce valid and practical PISA-like mathematics tasks in the context of Lake Aur and Pindang Musi Rawas and have a potential effect on students' ability to solve problems. This study used the design research method of the type of development studies with the preliminary stage and formative evaluation. In addition, in its implementation, problem development is also carried out through a lesson study system. The research subjects were class IX students of SMPIT Annida Lubuklinggau. Data was collected using walkthrough techniques, documentation, observation and questionnaire which were then analyzed using qualitative description methods to describe the results of each stage of development. This research produced sharing tasks in the context of Lake Aur and jumping tasks in the context of Pindang Patin Musi Rawas which are valid, practical as well as having a potential effect on students' mathematics ability to identify and solve PISA-like mathematics tasks. The results showed that the use of context and collaborative learning in solving PISA-like mathematics tasks made the questions easier to understand and the process more enjoyable. This is because the context of Lake Aur and Pindang Musi Rawas is known and close to students' daily lives and there is a process of teaching each other among fellow students.